Malnutrition in children under 5 years of age in Chisapani and Sutaiya (Banke) villages - Bhatia, V; Manandhar, N (Journal of Institute of Medicine Nepal, 2000)
Malnutrition is one of the major public health problems in developing countries including Nepal. Malnutrition not only directly affects the children by reducing their physical and mental performance but also makes the situation worse by making the child susceptible to infections. The long-term effects of malnutrition also need to be highlighted. Those suffering from malnutrition in early parts of their life tend to have lower weight even during adult life. The physical work capacity is hence reduced. The present study was conducted in the rural areas of Chisapani and Sutaiya (Banke). The total sample size taken in the study was 137. The study was conducted with the help of 5 volunteer students of the college. The anthropometric measurements of children were taken. To assess the degree of malnutrition the weight/height (length) ratio was compared to the WHO/NCHS standards and stunting was also taken into account. The result puts the total of malnourished children in the study group to 63 (46.4%). On drawing comparisons, malnutrition was found to be associated with female sex, joint family and the total number of children in the family. It is thus felt that the children in these villages need special attention. This can be done by providing nutritional education to the parents and among other things by bringing on a social change so that the female child is not neglected.